Effects of Veratrilla baillonii Extract on Hepatic Gene Expression Profiles in Response to Aconitum brachypodum-Induced Liver Toxicity in Mice - Li, Jun; Liu, Gang; Ihsan, Awais; Yi, Xuejia; Wang, Da-Gui; Cheng, Han; Muhammad, Azhar; Huang, Xian-Ju (Frontiers in Pharmacology, 2019)
This manuscript was aimed to explore the hepato-protective effect of water extract of Veratrilla baillonii Franch. (Gentianaceae) (WVBF) on serious hepatic toxicity induced in mice treated with Aconitum brachypodum Diels (Ranunculaceae) at transcriptome level. The physiological and pathological symptoms were evaluated as the markers for hepato toxicity induced by A. brachypodum Diels (CFA) extracted compounds. Moreover, gene chip method was used to compare and investigate the gene expression level of WVBF on CFA induced-liver toxicity to identify the potential target of WVBF and CFA on liver. The results showed that WVBF had a significant detoxification effect on CFA-induced acute hepatic toxicity. There were 130 genes with lower expression and 124 genes expressed at higher rate in CFA treated group as compared with normal control group, while there are 67 genes down-regulated and 74 genes up-regulated in WVBF treated group in comparison with CFA treated group. WVBF could attenuate CFA-induced liver damage in mice through regulating oxidative stress, inflammatory injury and cell apoptosis/necrosis pathways. On the other hand, WVBF and CFA may have potential synergetic effects on the target genes of certain diseases such as inflammation, cancer and diabetes.